DEVELOPMENT OF PRESERVED-LEAVES LEARNING MEDIA ON PLANT MORPHOLOGY COURSE (Universitas PGRI Sumatera Barat, 2021)
Learning media plays an important role in learning outcomes. This study aims to determine the feasibility of the developed of preserved- leaves media. This type of research is research and development with the Dick and Carey Models. The research started from the phase of needs analysis, development, design, implementation, validation and product testing. Data were collected using scala likert, processed using the percentage formulaÂ and analyzed descriptively. The test results on the product are very valid for the theory aspect (88.75%) and media aspect (83.67%), very practical (score 81.67% on the aspects of interest and ease to use), and very feasible (score 86, 25% for the small group test and 90.50% for the large group test). Thus, Â concluded that the preserved-leaves media is valid, practical and feasible to use for plant morphology course.